(untitled) (Ustozlar uchun, 2025)
Abstract: The cutting process is one of the most fundamental operations in mechanical engineering, directly influencing the dimensional accuracy, surface integrity, and overall performance of manufactured components. Improving the quality of cutting involves optimizing multiple parameters such as cutting speed, feed rate, tool geometry, lubrication, and material properties. This paper investigates modern approaches to enhancing the cutting process through advanced tool materials, computer numerical control (CNC) optimization, and sustainable manufacturing techniques. The study also highlights the role of process monitoring and adaptive control systems in minimizing tool wear and ensuring consistent product quality. The results indicate that integrating sensor-based control, precision tooling, and eco-friendly cooling systems can significantly increase efficiency and reduce production costs.